THE ANALYSIS OF CONTROL RAW MATERIAL INJECTION PHYTON IN THE IMPLEMENTATION OF ECONOMIC ORDER QUANTITY (EOQ) IN PT. VICTORY CHYNGLUH INDONESIA - Surachman, Surachman; Handayani, Umi Mafida Ustahiroha (Yayasan Education and Social Center, 2022)
This study aimed to determine the inventory control of Python Injection (IP) raw materials at PT. Victory Chyngluh Indonesia. The method used in achieving data analysis objectives is to use the Economic Order Quantity (EOQ) form. Research results with the total cost of inventory using company policy are Rp. 2,622,540,500, - after using the Economic Order Quantity (EOQ) method is Rp. 2,419,006.133,-, thus the company can save the cost of raw material inventory for Python Injection (IP) of Rp.203,534,367,-